Tentoonstelling De Vijf : Jan Cantré,Jozef Cantré, Frans Masereel, Joris Minne, Henri Van Straten - Lebeer, Louis (Mechelen : Stad Mechelen, 1967)
Bibliotheek Jan Baghus
Nederlands
Brochure
Keywords: Masereel, Frans; kunst